2019
DOI: 10.1002/batt.201900134
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur‐Doped Carbon‐Wrapped Heterogeneous Fe3O4/Fe7S8/C Nanoplates as Stable Anode for Lithium‐Ion Batteries

Abstract: High‐capacity electrode materials have attracted tremendous attention in energy storage systems. However, the large volume expansion always causes breakdown of electrode materials and capacity fading. In this work, we report the preparation of heterogeneous Fe3O4/Fe7S8/C nanoplates with a high lithium diffusion coefficient and excellent lithium storage performance. The heterogeneous nanoplates can be derived from Fe‐MOF octahedra during the sulfidation process. As an anode for lithium‐ion batteries, the Fe3O4/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 46 publications
(87 reference statements)
0
16
0
Order By: Relevance
“…Both EIS profiles recorded in Figure S10 display a semicircle in the high frequency followed by a single line in the low frequency region. Note that the semicircle recorded for α‐MnS/MnO is much larger than that for α‐MnS/MnO/SCPF, indicating a lower impedance of the latter and further confirming the substantially enhanced Li‐ion and electron transport within the as‐fabricated composite material (i. e., α‐MnS/MnO/SCPF) [13,16] …”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…Both EIS profiles recorded in Figure S10 display a semicircle in the high frequency followed by a single line in the low frequency region. Note that the semicircle recorded for α‐MnS/MnO is much larger than that for α‐MnS/MnO/SCPF, indicating a lower impedance of the latter and further confirming the substantially enhanced Li‐ion and electron transport within the as‐fabricated composite material (i. e., α‐MnS/MnO/SCPF) [13,16] …”
Section: Resultsmentioning
confidence: 61%
“…Herein, we report the facile sulfidation process to fabricate micro‐rod composites consisting of heterostructured α‐MnS/MnO NPs and an S‐doped carbon‐based porous framework (denoted as α‐MnS/MnO/SCPF), starting from a Mn‐based metal‐organic framework (Mn–MOF) as the only precursor. Despite some progress in MOF‐derived, heterostructured metal composites, the synthesis of such Mn‐based composites by using MOF‐driven approach is, to the best of our knowledge, reported here for the first time [16] . Herein, we systematically studied the physicochemical features and the Li‐ion storage performance of the as‐obtained composite.…”
Section: Introductionmentioning
confidence: 99%
“…[89] Reproduced with permission. [125] 5b,c). It has been reported that multi-anion electrodes experience multi-step electrochemical reactions and some additional reactions, which results in the enhancement of reversible capacities.…”
Section: Cycle and Rate Performancesmentioning
confidence: 97%
“…Pan's group experimentally obtained the GITT curves of Fe 3 O 4 /Fe 7 S 8 /C electrodes with heterointerfaces, Fe 3 O 4 /C, and Fe 7 S 8 /C electrodes to verify the effect of the heterostructure. [ 125 ] The GITT curves of the three electrodes were used to calculate the Li + ion diffusion coefficients using the above equation, and the log D values versus lithiation/delithiation states are shown in Figure 5 a. [ 125 ] Fe 3 O 4 /Fe 7 S 8 /C composite electrode materials exhibited higher D values during the charge and discharge processes compared to electrodes with single anions.…”
Section: Theoretical and Experimental Understanding Of Heterostructure Effects And Analytical Tools For Identification Of Components In Hmentioning
confidence: 99%
See 1 more Smart Citation